Community Participation in Village Owned Enterprise Governance: A Study of Karya Bakti Village Owned Enterprise in Wiwitan Timur Village - Musafir Jasin; Amra Amra (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze community participation in the governance of Karya Bakti Village-Owned Enterprise (BUMDes) in Wiwitan Timur Village. The research focuses on examining the forms and roles of community participation in supporting the governance of BUMDes as a village economic institution. To address this issue, the study adopts Cohen and Uphoff's theory of community participation and the concept of participatory governance in public organizational management as its theoretical framework. The study employed a qualitative approach using a descriptive research design. Data were collected through interviews, observations, and document analysis involving village government officials, BUMDes management, members of the Village Consultative Body (BPD), community leaders, and residents of Wiwitan Timur Village. The collected data were analyzed qualitatively through the stages of data reduction, data display, and conclusion drawing. The findings indicate that community participation has occurred in the stages of decision-making, program implementation, as well as the monitoring and utilization of BUMDes outcomes. However, the level of participation varies across these stages. Community involvement is more prominent in activities that provide direct economic benefits, whereas participation in decision-making and monitoring processes remains relatively limited and requires further enhancement. The study concludes that the success of BUMDes governance is strongly influenced by community participation, management transparency, and the ability of BUMDes administrators to foster effective communication and public trust.